Managing xylazine-involved overdoses in a community harm reduction setting: lessons from Tijuana, Mexico - Lilia Pacheco Bufanda; Alejando González Montoya; Brenda Torres Carrillo; Mariana Alejandra Gonzalez Tejeda; Luis A. Segovia; Alhelí Calderón-Villarreal; Joseph R. Friedman (Harm Reduction Journal)
Abstract Background Xylazine is a α2-adrenergic receptor agonist, used for sedation in veterinary contexts. Although it is increasingly found in overdose deaths across North America, the clinical management of xylazine-involved overdoses has not been extensively studied, especially in community-based harm reduction settings. Here we present a clinical series of xylazine-involved overdose and share the clinical approach and lessons learned by a community overdose response team in Tijuana, Mexico amidst the arrival of xylazine. Case Presentation We present three cases describing the clinical management of patients with xylazine-involved overdoses that occurred in close proximity to the Prevencasa community harm reduction clinic. The long period of post-naloxone sedation in xylazine overdoses is a unique clinical feature. The first case is a 61-year-old man with longstanding opioid and methamphetamine use disorder found hypoxic, who received 4.0 mg of intranasal naloxone, and quickly began respirating well. He remained unconscious for 20 min, and upon awakening, experienced withdrawal symptoms, agitation and confusion, and exposed himself to considerable physical danger by entering a local roadway. The second is a 28-year-old man who primarily uses stimulants, who overdosed while trying “China White”. His oxygen saturation improved from 81 to 100% with supplemental oxygen and field management, and he did not require naloxone administration. He recovered consciousness after 40 min. The third patient is a 36-year-old male who was found down, saturating at 20%, who received 0.4 mg intramuscular naloxone, was placed in recovery position, and remained unconscious for 12 min before making a complete recovery. The first and third patients provided urine and drug samples that tested positive for xylazine and fentanyl. Conclusions We describe insights about the clinical management of combined xylazine-fentanyl involved overdoses in the field, from a community harm reduction context where xylazine arrived suddenly spurring a large number of overdoses. In response to the long period of post-naloxone sedation inherent to xylazine overdoses, the clinical team learned to center oxygenation—not consciousness—as the key parameter of interest for the titration of naloxone, increase emphasis on field airway management, portable oxygen administration, and scene safety, and employ xylazine testing strips for urine and direct substance analysis to educate the patient population about health risks.